Kajian Hukum Kekuatan Pembukian Akte Notaris Dibandingkan Akte Di bawah Tangan Yang Berlaku Di Indonesia - Sumarno, Edy (LP3M Universitas Islam Zainul Hasan Genggong, 2023)
Abstract Since 1996 any transfer of land rights must be carried out with an authentic deed drawn up by an authorized official, according to Government Regulation Number 10 of 1961 article 19, now it has been replaced by Government Regulation Number. 24 of 1997 article 37 concerning land transfers, which states that any agreement that intends to transfer land rights, must be proven by a deed drawn up before an authorized official, namely the Land Deed Making Officer (PPAT). In the provisions of Government Regulation Number 24 of 1997 it has been determined that the Land Deed Making Officer (PPAT) must refuse to make a transfer deed or burden of debt with guaranteed land rights. In rural communities, the process of owning land rights is sometimes only done verbally, trust or mutual trust and is written in a simple manner, then reported orally to village officials and followed up by recording it in a krawangan book or letter C book. Ownership of land rights by this process is very vulnerable to disputes between parties making the transition, abuse by people who have interests, and do not have strong authentic evidence. The problem approach in this study is Normative Juridical where the focus of the study is the norms contained in Government Regulation Number 10 of 1961 article 19, which has now been replaced by Government Regulation Number. 24 of 1997 article 37 concerning land transfer. The analysis of this study used a qualitative descriptive method, namely an analytical study in a coherent, complete and clear manner based on the data obtained by the researcher. The purpose of this research is to find out how to get rights to land that are legally and firmly owned in accordance with existing regulations in Indonesia. Keywords: Land ownership, evidence, certificate, Indonesia